ASUHAN KEPERAWATAN KELUARGA DIABETES MELLITUS DENGAN MASALAH KETIDAKSTABILAN KADAR GLUKOSA DARAH - Kurniawati; Dwiharini Puspitaningsih (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
Succes in treating diabetes mellitus patients requires a family role. One of the family roles of diabetes mellitus patientsis controlling blood sugar levels of diabetes mellitus patients. This study aimed to provide diabetes mellitus family nursing care with an inability to controll blood sugar levels.The design usedinthis research was a case study. The study used 2 families. Then diagnosed nursing intervention, implementation and evaluation. Data collection methods by interview, observation, and documentation using the family nursing care format.The result of the assesment of the two families showed the same results, namely were not knowing and were being unable to controlling blood sugar levels. After conducting three interventions which included counseling and assistance in iscontrolling blood sugar levels, which was carried out three times, the result werethat the family undestood andwere able tocontrollingbloodsugarlevels of diabetes mellitus patients. Controlling blood sugar levels of diabetes mellitus patient sathomeislargely determined by the roleofthe family.